2009
DOI: 10.1016/j.jtbi.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial usage on the transmission dynamics of antimicrobial resistant bacteria among pigs

Abstract: There is increasing evidence showing that antimicrobial consumption provides a powerful selective force that promotes the emergence of resistance in pathogenic, commensal as well as zoonotic bacteria in animals. The main aim of this study was to develop a modeling framework that can be used to assess the impact of antimicrobial usage in pigs on the emergence and transmission of resistant bacteria within a finisher pig farm. The transmission dynamics of drug-sensitive and drug-resistant bacteria among pigs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Our model predicted that the use of antimicrobials increase the level of resistant bacteria in a population, which is in concordance with the surveillance of Danish pigs [3] and other similar models [6], [15], [25]. We further demonstrated that besides the expected rise within-pig due to the growth of resistant strains during treatment, the increased levels of bacteria following treatment may also increase the transmission of resistant strains between pigs in a pen.…”
Section: Discussionsupporting
confidence: 87%
“…Our model predicted that the use of antimicrobials increase the level of resistant bacteria in a population, which is in concordance with the surveillance of Danish pigs [3] and other similar models [6], [15], [25]. We further demonstrated that besides the expected rise within-pig due to the growth of resistant strains during treatment, the increased levels of bacteria following treatment may also increase the transmission of resistant strains between pigs in a pen.…”
Section: Discussionsupporting
confidence: 87%
“…Interaction and competition between useful bacteria, particularly of the genus Lactobacillus, and pathogenic taxa of the family Enterobacteriaceae play a key role in the functioning of the digestive tract in pigs (21). Potentially pathogenic bacteria in the gastrointestinal tract of animals in favorable conditions can multiply and lead to the emergence and spread of factors of resistance to certain antibiotics (1,3,5,6,14).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…Without antimicrobial exposure, a fitness cost for the resistant strain, which often translates in a faster recovery rate or lower transmissibility, is assumed (Levin, 2001). Abatih et al (2009) used this approach to evaluate the effect of antimicrobial usage on the transmission of antimicrobial resistant bacteria among pigs. They concluded that control measures that reduce the transmission rate or increase the spontaneous clear-out rate for resistant bacteria would reduce the proportion of pigs with drug-resistant bacteria before transport to slaughter (Abatih et al, 2009).…”
Section: Transmission Modelingmentioning
confidence: 99%
“…Abatih et al (2009) used this approach to evaluate the effect of antimicrobial usage on the transmission of antimicrobial resistant bacteria among pigs. They concluded that control measures that reduce the transmission rate or increase the spontaneous clear-out rate for resistant bacteria would reduce the proportion of pigs with drug-resistant bacteria before transport to slaughter (Abatih et al, 2009). Empirical studies in which transmission of resistant and sensitive strain are measured are needed to validate such conclusions.…”
Section: Transmission Modelingmentioning
confidence: 99%